2007
DOI: 10.1111/j.1442-200x.2007.02450.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between white blood cell count and metabolic syndrome in adolescence

Abstract: In adolescents with normal WBCC, BMI is significantly related to the levels of WBCC and is the earliest component of MetS to be noted in adolescents. Elevated TG and decreased HDL-C could also be important markers for future risk factors only in male subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…In adolescents with normal WBC and no history of significant medical diseases, BMI was shown to be significantly related to the WBC level (Hsieh et al, 2007). These investigators also reported that these two markers are the earliest components of MS. Additionally, Farhangi et al (2013) reported that obese women had higher WBC levels, platelet counts, and inflammatory biomarkers compared with non-obese healthy women.…”
Section: Statistically Significant Relationship Between Ptss and Chd mentioning
confidence: 84%
See 1 more Smart Citation
“…In adolescents with normal WBC and no history of significant medical diseases, BMI was shown to be significantly related to the WBC level (Hsieh et al, 2007). These investigators also reported that these two markers are the earliest components of MS. Additionally, Farhangi et al (2013) reported that obese women had higher WBC levels, platelet counts, and inflammatory biomarkers compared with non-obese healthy women.…”
Section: Statistically Significant Relationship Between Ptss and Chd mentioning
confidence: 84%
“…Our findings are in agreement with those of a previous study. In adolescents with normal WBC and no history of significant medical diseases, BMI was shown to be significantly related to the WBC level (Hsieh et al., ). These investigators also reported that these two markers are the earliest components of MS. Additionally, Farhangi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hoffman et al [23] showed that the value of WBC count in predicting cardiovascular disease was similar to serum cholesterol and BP. Moreover, recent studies have shown that WBC count was associated with metabolic syndrome in adults and children receiving routine health examinations [7,26]. Furthermore, circulating macrophage levels have been shown to correlate with fat mass and to predict outcome in patients with chronic kidney disease [27].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies had demonstrated a correlation between WBC count, type 2 diabetes, and CVD [5][6][7][8][9]. Moreover, the correlation between WBC count and MetS has been further demonstrated using different ages, genders and races [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%